ADSORPTION CHARACTERISTICS OF METRONIDAZOLE FROM INDUSTRIAL WASTEWATER ONTO POLYANILINE NANOCOMPOSITE: Life Science-Biotechnology - BALARAK, DAVOUD; HOSSEIN MANSOURI, AMIR; CHANDRIKA, KETHINENI (International Journal of Life Science and Pharma Research, 2019)
Over the past few decades, occurrence of organic micro-pollutants such as pharmaceuticals in the aquatic ecosystems has been considered as a major environmental and health issue globally. Pharmaceuticals have become chemicals of emerging concern to the public because of their potential to reach drinking water. A novel Polyaniline/humic acid (PA/AH) composite was synthesized and investigated for adsorption of Metronidazole antibiotics (MTZ) from aqueous solutions. The nature and morphology of synthesized adsorbent were characterized by scanning electron microscope, Surface adsorption (BET). Batch experiments were performed to study the influence of various experimental parameters such as contact time, initial concentration of the MTZ and temperatures at fixed solution pH and adsorbent dosage. A comparison of kinetic models was evaluated for the pseudo-first-order, pseudo-second-order, Elovich, intraparticle diffusion and Bangham’s kinetics models. The experimental data fitted very well the pseudo second-order kinetic model and also followed by intra-particle diffusion model; whereas diffusion is not only the rate-controlling step, and likely that both adsorption steps, bulk and intra-particle diffusion, control the rate of adsorption process. The results show that the sorption capacity increases with increase in solution temperature from 10 to 55 oC. As adsorption capacity of 42.2 to 49.95 mg/g increases when the temperature increases from 10 to 55 oC. The developed polyaniline nanocomposites in this study have considerable potential for the removal of MTZ and could be considered as a promising adsorbent for the removal of other antibiotics also from aqueous solutions.